YTHDC2-Mediated circYTHDC2 N6-Methyladenosine Modification Promotes Vascular Smooth Muscle Cells Dysfunction Through Inhibiting Ten-Eleven Translocation 2 - Yuan, Jun; Liu, Yu; Zhou, Lizhen; Xue, Yan; Lu, Zhengde; Gan, Jianting (Frontiers in Cardiovascular Medicine, 2021)
Type 2 diabetes condition mediated vascular smooth muscle cell (VSMCs) dysfunction. However, the mechanism of VSMCs dysfunction in diabetic patients needs further elucidation. VSMCs are an important component of the vascular wall, participate in the process of vascular remodeling, and play a vital role in the vascular complications of diabetes. Studies have found that circular RNAs (circRNAs) play a key regulatory role in the occurrence and development of VSMCs dysfunction. In this study, we stimulated VSMCs with high glucose and identified a new circular RNA, circYTHDC2, using circRNA chip analysis. circYTHDC2 was highly expressed in VSMCs treated with high glucose. Knockout of circYTHDC2 significantly inhibited the proliferation and migration of VSMCs. Metformin treatment significantly inhibited the expression of YTHDC2 and circYTHDC2. The upstream mechanism analysis revealed that the stability of circYTHDC2 was regulated by YTHDC2-mediated m6A modification. Furthermore, circYTHDC2 negatively regulates the expression of Ten-Eleven Translocation 2 (TET2) by targeting the unstable motif of TET2 3'UTR, thereby promoting dedifferentiated "synthetic type" transformation of VSMC. Taken together, these results suggest that the YTHDC2/circYTHDC2/TET2 pathway is an important target of metformin in preventing the progression of VSMCs dysfunction under high glucose.